A Framework for Assessing Socio-Economic Impact of Covid-19 at Household Level - Katuwal, Khagendra; Raut, Nirmal Kumar; Adhikari, Naveen (Tribhuvan University Journal, 2020)
The governments across the world have adopted measures to contain the spread of virus which has resulted into restricted economic activities. While economic impacts are diverse and wide spread, the interest in examining impacts at household level is of utmost importance from policy perspectives. This helps monitoring the progress of major socio-economic indicators and make timely and appropriate policy responses. In this context, this perspective paper outlines methodology to be adopted in examining the impacts of COVID-19 in number of household level indicators based on the literatures of impact evaluation. This paper also outlines a framework for identifying key priorities areas with particular reference to Nepal. We propose standard household health production function model with a use of quasi-experimental design as a candidate to examine the impacts at the household level. Likewise, indicators pertaining to poverty, food and nutrition, education, health and labor market are of primary interest with reference to Nepal's development aspirations and trajectory. We expect that this paper will contribute in choosing suitable methodology for assessing impacts at household level and understanding the policy and data context in Nepal.